Analysis of the Islamic Cultural History Curriculum - Retno Dwi Ramadhannita; Mulyawan Safwandy Nugraha (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Islamic Cultural History Curriculum Analysis is an in-depth review of the structure and content of the curriculum relating to Islamic history and culture. This research evaluates the philosophical, theological, sociocultural, psychological and science and technology foundations. The analysis of the history of Islamic education curriculum also provides a foundation for efforts to improve the quality of Islamic education. Evaluation of the curriculum helps identify strengths and weaknesses, so that continuous improvement can be made. The focus of the analysis includes learning objectives, teaching materials, learning resources, and evaluation. The purpose of this study was to analyze the Islamic cultural history curriculum, especially in the Riyadhul Jannah Modern Junior High School with a qualitative case study approach. The results of the analysis of the Islamic cultural history curriculum in general went well with the appropriate planning and implementation stages.